Bank Health Analysis at PT. Bank NTB Syariah With Risk Based Bank Rating and Financial Distress Method - Nurul Hidayati Indra Ningsih Nurul; Baiq Reinelda Tri Yunarti; Mos Indrawati (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to determine the health level of PT Bank NTB Syariah in 2019-2020. This research uses quantitative research. The data collection method used in this research is the documentation method. The data analysis technique used is to analyze financial statements in accordance with PJOK Number 8/POJK.03/2014 CHAPTER II Article 6 No. 1 and Article 2 Bank Indonesia Regulation No. 13/1/PBI/2011. The results of the study show that the risk profile or risk profile of Bank NTB Syariah in 2019 and 2020 seen from the NPF value obtained a healthy predicate, while if viewed from the FDR value in 2019 the NPF value received a healthy predicate, but in 2020 it received a Fairly Healthy predicate. Earnings or Profitability of Bank NTB Syariah in 2019 and 2020 obtained the title Very Healthy as reflected in the ROA ratio value of more than 1.5% Capital or Bank NTB Syariah capital in 2019 and 2020 obtained the predicate very healthy as reflected in the calculation of the CAR ratio exceeding the limit 12%. Based on the Self-Assessment in the report on the implementation of Good Corporate Governance, Bank NTB Syariah in 2019 and 2020, obtained a composite rating of 2 with the